'Asbaanjaers Rig Oë Op Pretoria': A Short History of Stock-Car Racing in South Africa's Capital City. Issue 3 (3rd May 2020) - Pieterse, Jimmy
Abstract : This article outlines the history of stock-car racing in South Africa's capital city until 1968. By reconstructing the histories of two raceways in Pretoria, it shows how stock-car and oval-track racing helped to (re)inscribe the cityscape. It draws attention to the contentious, at times symbiotic, relationship between the city council and the sport of stock-car racing in the context of shifting ideas around the respectable consumption of automobiles. It also analyses the entwinement of this history with other pastimes/subcultures. Finally, it shows that involvement (whether as participants or spectators) in oval-track racing created the conditions necessary for the production of alternative yet completely viable scripts of how to be white in Pretoria during the 1950s and the 1960s. Evidence is drawn from archival sources, popular print media, and ethnography.